2019 16th International Symposium on Wireless Communication Systems (ISWCS) 2019
DOI: 10.1109/iswcs.2019.8877287
|View full text |Cite
|
Sign up to set email alerts
|

Framework for the Identification of Rare Events via Machine Learning and IoT Networks

Abstract: This paper introduces an industrial cyber-physical system (CPS) based on the Internet of Things (IoT) that is designed to detect rare events based on machine learning. The framework follows the following three generic steps: (1) Large data acquisition / dissemination: A physical process is monitored by sensors that pre-process the (assumed large) collected data and send the processed information to an intelligent node (e.g., aggregator, central controller); (2) Big data fusion: The intelligent node uses machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Difficulties related to these tasks originate from the fact that anomalies are rare events within datasets, making it difficult to apply most of the existing algorithms which result in either false alarms or misdetections [13], [14]. The authors of [8] made an attempt at providing a general framework to model a wide range of cases based on the advances in IIoT networks and Machine Learning (ML) algorithms. Similarly, the authors of [15], [16] describe several deployed solutions of cyber-physical systems in an industrial environment.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Difficulties related to these tasks originate from the fact that anomalies are rare events within datasets, making it difficult to apply most of the existing algorithms which result in either false alarms or misdetections [13], [14]. The authors of [8] made an attempt at providing a general framework to model a wide range of cases based on the advances in IIoT networks and Machine Learning (ML) algorithms. Similarly, the authors of [15], [16] describe several deployed solutions of cyber-physical systems in an industrial environment.…”
Section: State Of the Artmentioning
confidence: 99%
“…This analysis showed that only 12 sensors have a significant impact on the fault classification mechanism. The set S C of critical sensors is 8,12,17,18,20,21,43,44,49, 50, 51}. Some of these sensors impact multiple faults (e.g.…”
Section: Gan-based Missing Data Imputationmentioning
confidence: 99%
See 1 more Smart Citation
“…The work proposed in this article is based on the FIREMAN project funded by the CHIST-ERA programme, which focuses on modelling and analysing IIoT networks based on specific machine learning algorithms capable of detecting rare events in industrial setups in an ultra-reliable way [8]- [10] important aspect in assuring such ultra-reliability in the IIoT is how to guarantee we have a functioning system in place, even in case some of the measurements are missing due to network or hardware issues. In fact values are often missing from the collected sensor data, and the related issue of missing value imputation becomes then very important.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we deal with this problem by proposing a general frame to model a wide range of cases based on the advances in Industrial Internet of Things (IIoT) networks and Machine Learning (ML) algorithms [3]. In particular, we approach the problem by using a theory that considers three autonomous (but strongly dependent) layers of cyber-physical systems (CPS), namely physical, data and regulatory.…”
Section: Introductionmentioning
confidence: 99%